CULTURAL DIALOG AS A FACTOR OF SOCIO-CULTURAL DYNAMICS IN MODERN CONDITIONS (Revista Inclusiones, 2020)
The relevance of this study stems from the growing complexity of social relations, where dialog as a sociocultural phenomenon becomes an important means for understanding different levels of communication. The necessity of studying cultural dialog is a result of the contradictory crisis processes in modern society. In this society, the main condition of tolerant conflict resolution is dialog as a form of the interest alignment. Dialog increasingly often serves as an only possible way of the survival of mankind. In this regard, this paper studies the phenomenon of cultural dialog in the conditions of modern sociocultural reality. The intensity of sociocultural changes related to the processes of transculturation, integration and information, affects the ways of cultural interaction. It also concludes about the need to solve the following tasks: to analyze the subject matter of dialog as a form of intersubject interaction; to consider cross-cultural dialog as a priority strategy for crosscultural interaction in modern conditions; to conclude about the place of Russia in modern cultural dialog; describe the consolidating role of political dialog; to identify the features of cultural dialog in the information and communication space. A leading approach to the study is a philosophical and cultural approach that allows revealing the nature, essence and ways of implementing cultural dialog in modern conditions. The paper substantiates the possibility and necessity of communication between the cultures, each of which carries its own meanings, traditions and norms.